2014
DOI: 10.1002/nau.22633
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of urodynamic pressures measured simultaneously by air-charged and water-filled catheter systems

Abstract: The developed algorithm can be used to convert rapidly changing urodynamic pressures, such as cough leak point pressure, obtained using ACC systems to corresponding values expected from WFC systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…They found that the mean MUCP was significantly lower for the water perfusion catheter compared with the microtip transducer catheter . Awada et al showed that air‐charged catheters significantly underestimated the peak pressures of rapidly changing pressures, such as during coughs, compared with those measured by water‐filled catheters. Another study determined that air‐charged and water‐filled catheters cannot be assumed to register equal values of pressure and differed by up to 10 cmH 2 O .…”
Section: Discussionmentioning
confidence: 99%
“…They found that the mean MUCP was significantly lower for the water perfusion catheter compared with the microtip transducer catheter . Awada et al showed that air‐charged catheters significantly underestimated the peak pressures of rapidly changing pressures, such as during coughs, compared with those measured by water‐filled catheters. Another study determined that air‐charged and water‐filled catheters cannot be assumed to register equal values of pressure and differed by up to 10 cmH 2 O .…”
Section: Discussionmentioning
confidence: 99%
“…The balloons are batch calibrated, and identical AFCs are used for bladder, vaginal, and rectal pressure measurements. The critical maximum frequency response of the T‐Doc is approximately 3 Hz and this is too low to capture the most rapid changes in pressure, such as during coughs and cough leak point pressure measurement . The suggestion that bandwidths of up to 14–15 Hz are required to accurately reproduce rapidly changing urodynamic pressures has been endorsed by both the earlier and the latest ICS Guidelines on Urodynamic Equipment Performance.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that AFCs are capable of recording bladder pressures during voiding accurately, but that T‐Doc AFCs will likely attenuate the bladder pressure (i.e., record a lower bladder pressure than actual pressure) during coughing, since coughs cause a much faster rise in bladder pressure than voiding. WFCs can likewise record bladder pressures during voiding accurately, but in contrast to AFCs, can potentially amplify the bladder pressure during cough tests …”
Section: Methodsmentioning
confidence: 99%
“…We validated that air‐charged catheters are overdamped while water‐filled catheters are underdampled. Peak pressures recorded simultaneously by air‐charged catheters and water‐filled catheters became more similar as the time to peak pressure increased, and differed significantly for events lasting less than 0.5 sec, such as a cough leak point pressure, with peak pressures measured by air‐charged catheters significantly underestimating those measured by water‐filled catheters during rapidly changing signals . From these data, we empirically derived and validated an equation that utilizes peak pressure and time to peak pressure measured by air‐charged catheters to predict what the peak pressure would have been had it been measured by a water‐filled catheter.…”
Section: Dear Editormentioning
confidence: 98%
“…Therefore, we embarked on our second study in which cough leak point pressure, as an example of a urodynamic test with rapidly changing pressures, and valsalva leak point pressure, as an example of a urodynamic test with more slowly changing pressures, were utilized to continue to test air‐charged and water‐filled catheters in the highly controlled environment of the benchtop pressure chamber. We validated that air‐charged catheters are overdamped while water‐filled catheters are underdampled.…”
Section: Dear Editormentioning
confidence: 99%